2008
DOI: 10.1063/1.2986230
|View full text |Cite
|
Sign up to set email alerts
|

Spinwave propagation and coupling in magnonic waveguides

Abstract: Critical behavior of two-dimensional spin systems under the random-bond six-state clock model J. Appl. Phys. 112, 063924 (2012) Effect of spin drift on spin accumulation voltages in highly doped silicon Appl. Phys. Lett. 101, 122413 (2012) Spin-wave excitations induced by spin current through a magnetic point contact with a confined domain wall Appl. Phys. Lett. 101, 092405 (2012) Spin-torque effect on spin wave modes in magnetic nanowires Appl. Phys. Lett. 101, 072409 (2012) The influence of in-plane fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The Snell's law in Eq. (3) is derived for an interface (domain wall) formed by two opposite magnetic domains in a single magnetic material, thus it is completely different from the Snell's laws that were derived for an interface between two regions with different magnetic properties [24,25]. In addition, Eq.…”
mentioning
confidence: 90%
“…The Snell's law in Eq. (3) is derived for an interface (domain wall) formed by two opposite magnetic domains in a single magnetic material, thus it is completely different from the Snell's laws that were derived for an interface between two regions with different magnetic properties [24,25]. In addition, Eq.…”
mentioning
confidence: 90%
“…We observed that wavenumber of the spin wave passing through the junction doubles reflecting the thickness difference. According to Snell's law, the relative refraction factor is defined as the phase velocity [6]. Because the dispersion of the MSSW depends on product of the wavenumber and the thickness, the relative refraction factor of the spin wave is proportional to inverse the thickness.…”
Section: Methodsmentioning
confidence: 99%
“…which is the law of refraction for spin waves, or called the magnonic Snell's law [28][29][30][31][32][33][34] . Figure 3(b) is the θ t -ω/2π curve at θ i = 20 • .…”
Section: A P Configurationmentioning
confidence: 99%
“…It's worth noting that spin waves are thermally excited by the spin Seebeck effect (SSE) in the experiments of magnon valves 20 and magnon junctions 21 , thus the coherence of spin waves is ignored. In fact, the coherence is important for spin-wave transmission because it can lead to plentiful physical phenomena, such as refraction [28][29][30][31][32][33][34] , skin effect 35 , Goos-Hänchen (GH) shift [36][37][38][39] , tunneling 40 , resonant tunneling 41,42 and resonant transmission [43][44][45][46] . Therefore, the systematic researches on the transmission of coherent spin waves in P and AP magnetic configurations are necessary, however few studies have reported on this issue.…”
Section: Introductionmentioning
confidence: 99%